Research Trends of Polymer Film for Radiation Radiotherapy: A Review - Doyan, Aris; Susilawati, Susilawati; Annam, Syarful; Ikhsan, Muhammad; Ardianti, Nuraini Rachma (Balai Publikasi Indonesia, 2026)
Polymer-based radiation dosimeters have attracted significant attention in recent years due to their capability to measure complex radiation dose distributions in radiotherapy applications. This study aims to analyze the research trends related to polymer film and polymer gel dosimetry used in radiotherapy through a systematic literature review and bibliometric analysis. The study employed the PRISMA methodology to systematically identify and select relevant publications from the Scopus and SINTA databases. A total of 30 articles published between 2018 and 2025 were included in the analysis. Bibliometric analysis was conducted using VOSviewer to examine publication trends, keyword co-occurrence networks, and research collaboration patterns. The results indicate a steady increase in research publications related to polymer dosimetry over the past decade. Keyword clustering analysis revealed several dominant research themes, including polymer gel dosimetry, radiation polymerization, dose distribution measurement, polymer film dosimeters, and nanoparticle-enhanced polymer materials. Among these topics, polymer gel dosimetry remains the most widely studied due to its capability to record three-dimensional radiation dose distributions. However, recent studies have increasingly explored polymer film dosimeters and nanocomposite materials to improve radiation sensitivity and dosimetric performance. Overall, the findings highlight the rapid development of polymer dosimetry technologies and their growing importance in modern radiotherapy quality assurance. Future research should focus on developing advanced polymer nanocomposites and integrating imaging-based dosimetry techniques to improve radiation dose measurement accuracy and clinical applicability.